ROLE OF FLAG LEAF IN WHEAT YIELD - & et al., Hashim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field trail was conducted at the Field Crop Research Station, Abu-Graib of Agricultural Research Office during 2011-2012 and 2012-2013 in order to investigate the relationship between flag leaf and yield of four wheat varieties. Split plot arrangement with RCBD three replications was used. Varieties (Fatih, Abu-Graib3, Mexipack and IPA 99) was occupied main plots while, flag leaf removal treatments (control treatment (no removal), removal at complete emergence flag leaf (24 March), 29 March, 3 April, 8 April, 13 April and 18 April) was occupied as sub plots. The results showed significantly effect of flag leaf treatments to all studied characteristics (except spike length at second season only). The highest impact reached for removal at emergence flag leaf soon (24 March). Spike length reduced 10.31 and16.85, spikelet number per spike 15, 13%, number of grain per spike 24, 28%, grain weight 7.04, 9.65% and spike yield 30.1, 35.29% for first and second season respectively. Can be show reduced of flag leaf impact when advanced to maturity. Varieties were differed significantly in all characteristics studied. The highest spike length was attained for IPA-99, Fatih, number of spikelet per spike for Fatih, IPA-99, number of grain per spike for Mexipack, grain weight for Abu-Graib3, IPA-99 and spike yield for Mexipack for first and second season respectively. Significant interaction was occurred for all studied characters between flag leaf treatments and varieties. Mexipack and Abu-Graib3 varieties with control treatment gave the highest spike yield (2.130 and 2.15 g) for first and second season, respectively. It can be conclude the importance and significant of vital role of flag leaf to contribution of spike yield about 30.1-35.29% especially at early complete emergence stage of flag leaf in wheat.